Internalization of Higher Education in India : Existing Realities and Future Outlook - Ramanathan, Vanisree (Prabandhan: Indian Journal of Management, 2018)
Internationalization of higher education has been the focus in the globalized era to enhance the standards of educational institutions, which enabled them to produce skilled and knowledgeable workforce for an economy based on a globalized market. As globalization opened up enormous opportunities for India to engage with knowledge economies of the globe in order to build capacity and quality standards, relationship building and creating human resource capital through international links is vital. Internationalization of higher education demands multilevel initiatives from individuals, institutions, and the state. This paper analyzed the emerging trends, opportunities, and the multiple challenges experienced by India while internationalizing higher education. As education has been a state subject, multilevel interventions, from individuals, educational institutions, corporations, and the state are essential in the context of multiple challenges and roadblocks towards internationalization of education. A comprehensive policy, strategic planning, strict innovative regulatory framework to balance the public - private partnership along with independent monitory body and standardized practices are pre-requisites for India to become the magnet as a knowledge center in the emerging globalized economy.